2017
DOI: 10.3892/mmr.2017.6546
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane prevents bleomycin-induced pulmonary fibrosis in mice by inhibiting oxidative stress via nuclear factor erythroid 2-related factor-2 activation

Abstract: Lung fibrosis is associated with inflammation, apoptosis and oxidative damage. The transcription factor nuclear factor erythroid 2-related factor-2 (Nrf2) prevents damage to cells from oxidative stress by regulating the expression of antioxidant proteins. Sulforaphane (SFN), an Nrf2 activator, additionally regulates excessive oxidative stress by promoting the expression of endogenous antioxidants. The present study investigated if SFN protects against lung injury induced by bleomycin (BLM). The secondary aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 30 publications
1
40
0
1
Order By: Relevance
“…It upregulates the expression of endogenous antioxidant proteins against oxidative stress and damage via Nrf2 activation. In previous studies, sulforaphane was shown to rapidly cross the BBB in mice, leading to an increase in Nrf2 expression in the striatum and cortex (Alfieri et al, ; Bai et al, ; Tarozzi et al, ; Wang, Wu, et al, ; Yan et al, ; Zhao, Moore, Clifton, & Dash, ). SF is a potent activator of Nrf2 activator, which induces antioxidative effects through the Nrf2/ARE pathway in many diseases.…”
Section: Methodsmentioning
confidence: 96%
“…It upregulates the expression of endogenous antioxidant proteins against oxidative stress and damage via Nrf2 activation. In previous studies, sulforaphane was shown to rapidly cross the BBB in mice, leading to an increase in Nrf2 expression in the striatum and cortex (Alfieri et al, ; Bai et al, ; Tarozzi et al, ; Wang, Wu, et al, ; Yan et al, ; Zhao, Moore, Clifton, & Dash, ). SF is a potent activator of Nrf2 activator, which induces antioxidative effects through the Nrf2/ARE pathway in many diseases.…”
Section: Methodsmentioning
confidence: 96%
“…Catalase protects against oxidative stress-induced cell damage. Its activity and expression has been linked to many pathological processes, such as lung fibrosis (Yan et al, 2017). Catalase also activates this study may be due to the lower blood-alcohol concentration in maternal-fetal circulation and/or in the embryo than the other studies, which failed to activate SOD but was still high enough to achieve neural tube dysmorphogenesis in ethanol-exposed embryos.…”
Section: Discussionmentioning
confidence: 65%
“…Catalase protects against oxidative stress‐induced cell damage. Its activity and expression has been linked to many pathological processes, such as lung fibrosis (Yan et al, ). Catalase also activates Extracellular signal‐regulated kinase, thus stimulating cell growth that would otherwise be inhibited during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic pathways mainly include intrinsic and extrinsic pathways [ 43 ]. Some studies have confirmed that Nrf2/HO-1 mainly regulated apoptosis through intrinsic pathway, but relative studies about extrinsic pathway of Nrf2/HO-1 were few [ 44 , 45 ].In our study, Nrf2/HO-1 could suppress the expression of caspase-9 and caspase-3, and caspase-9 is the key factor of intrinsic pathway and active caspase-3 to induce apoptosis. Nrf2/HO-1 is probably concluded in the process of myocardial apoptosis after CME through the intrinsic pathway.…”
Section: Discussionmentioning
confidence: 99%